Glaciers of the northern massif of the Suntar-Khayata Mountains: current state and dynamics since the end of 1950s - B. R. Mavlyudov; M. D. Ananicheva (Лëд и снег, 2016)
The estimation of glaciers of the Suntar-Khayata Mountains (the Northeastern Siberia) in the context of previously published data is presented. Under the background of current warming the glaciers in this region retreat enough quickly, they decrease not only in a real size, but also by the ice thickness. In this paper the mean summer temperature and solid precipitation of the key factors for glaciation, which indicate unfavorable conditions for the glacier existence at present time are presented as spatial distribution of trends (for 45 years, until 2012). The glaciers of the northern massif of the Suntar-Khayata have a negative ice mass balance as their entire surface is below the equilibrium line altitude. Mean thickness of superimposed ice on the glaciers of this massif was about 17 cm. Based on the assumption of climate variation in the Northern Pacific data it is suggested about the beginning of more favorable climatic conditions for the Suntar-Khayata glaciers.